DigiField: Real-Time Smart Farming Monitoring System Using React.js and Express.js for Agricultural Digitalization - Auliana, Sigit; Octavian, Rizqi Kevin; Permana, Basuki Rahim Setya (JINAV: Journal of Information and Visualization, 2025)
The agricultural sector remains a cornerstone of Indonesia’s economy, yet it faces persistent challenges such as climate change, land degradation, and limited adoption of digital technology among smallholder farmers. One critical issue is the lack of real-time monitoring systems accessible to farmers for tracking essential environmental parameters such as soil moisture and temperature. Traditional manual methods are still widely used, leading to inefficiencies and suboptimal decision-making. This study proposes the development of DigiField, a smart farming monitoring system designed to bridge the technological gap in rural agriculture by leveraging modern web technologies. The system is developed using the React.js framework for the frontend, enabling a dynamic, responsive, and mobile-friendly user interface, and Express.js for the backend to facilitate real-time data processing from sensor devices. The research adopts a technology-based development approach, involving needs analysis from field observations and interviews with local farmers. The DigiField prototype is designed to monitor soil moisture and temperature using sensor data that is transmitted and visualized in real-time through a web interface. The system aims to support data-driven agricultural decision-making and enhance productivity through accessible, low-cost technology. Preliminary testing and user feedback indicate that DigiField is effective in addressing local agricultural monitoring needs, with a user interface that is intuitive for farmers and a backend infrastructure that supports real-time updates. This study contributes to both academic discourse in the field of agricultural informatics and practical efforts to promote digital transformation in Indonesia’s agricultural sector.